2019
DOI: 10.19087/jveteriner.2019.20.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Suplementasi Filtrat Jambu Biji dalam Pengencer AirKelapa-Kuning Telur terhadap Kualitas Semen Cair Sapi Bali (THE EFFECTIVENESS OF GUAVA FILTRATE SUPPLEMENTATION IN COCONUT WATER-EGG YOLK DILUTION ON QUALITY OF LIQUID SEMEN OF BALI CATTLE)

Abstract: The aim of this research was to know the effectiveness of guava filtrate supplementation in coconut water- egg yolk dilution on quality of liquid semen stored at 5oC of Bali cattle. Semen collected from a five year old Bali cattle using artificial vagina. Semen of good quality were kept in six tubes based on treatment then stored at 5oC. Treatments of the research were P0 : coconut water 80% + egg yolk 20% without guava filtrate; P1 : coconut water 80% + egg yolk 20% + 0.8% guava filtrate; P2 : coconut water 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In comparison, the average percentage of acrosome integrity is around 87.5%. This plasma membrane integrity percentage value is almost similar to the average results of study stated by Bebas et al, (2021), which reached around 83.55% but is still lower than the results of study conducted by Marawali et al, (2019), where membrane plasma and acrosome intgerity reached 90.16% and 90.12% respectively. Based on the evaluation of the macroscopic and microscopic characteristics of Bali bull semen, it can be concluded that the collected semen is of good quality and meets the requirements for further processing into frozen semen.…”
Section: Kinematics Of Bali Bull Semen After Freezingsupporting
confidence: 85%
“…In comparison, the average percentage of acrosome integrity is around 87.5%. This plasma membrane integrity percentage value is almost similar to the average results of study stated by Bebas et al, (2021), which reached around 83.55% but is still lower than the results of study conducted by Marawali et al, (2019), where membrane plasma and acrosome intgerity reached 90.16% and 90.12% respectively. Based on the evaluation of the macroscopic and microscopic characteristics of Bali bull semen, it can be concluded that the collected semen is of good quality and meets the requirements for further processing into frozen semen.…”
Section: Kinematics Of Bali Bull Semen After Freezingsupporting
confidence: 85%
“…ISSN 2721-1304, ISSN 2721ISSN -1207 Copyright © 2023, Journal La Lifesci, Under the license CC BY-SA 4.0 yolk, honey, and guava filtrate (Sumadiasa, et al, 2015;Astuti, 2018;Malik, et al, 2018;Marawali, et al, 2019). Nevertheless, the standard semen quality produced only lasts for 3-4 days.…”
mentioning
confidence: 99%